Socio-economic analysis of benefits of Ibadan urban forest reserves (2004)
This study examined the percentage distribution of benefits obtained from Ibadan urban forest reserves across policy relevant socio-economic classes of the populace in order to draw research and policy implications. Descriptive and inferential statistics were employed to analyse data obtained from a multi-stage random survey of 397 residents of Ibadan metropolis. The results show that benefits obtained from the urban forest reserves do not depend significantly on gender (x2=2.57; p>0.05), age-class (x2=8.58; p>0.05), educational-status (X2=7.24; p>0.05) and income-level (x2=5.05; p>0.05) of the respondents. The results also reveal the importance of these reserves as sources of medicinal plants for the health care of the metropolitan residents. These results buttress the pertinence of investigating the needs of different socio-economic classes of the public before development projects are initiated. It is recommended for managers of Ibadan urban forest reserves to set aside portions of the reserves for the conservation and multiplication of medicinal plants.